STUDENT PERCEPTIONS ON THE ACADEMIC STAFF SERVICE QUALITY AT BUNG HATTA UNIVERSITY INDONESIA - Yeasy Darmayanti; Daniati Puttri; Neva Novianti; Siti Rahmi; Suryadimal Suryadimal; Nor Azilah Husin (AKUNTABILITAS, 2023)
Optimizing services to students is an important aspect that must be managed seriously by all tertiary institutions. Moreover, with the PT-BHMN regulation, state universities also play a role like private universities in reaching the number of students. Therefore, service is one of the key factors and promotional media for prospective students in choosing a tertiary institution. In this study, we investigated student perceptions of the service quality of academic staff at Bung Hatta University. Data was collected from 488 students. Sample data were statistically analyzed using the modified Servqual model using 6 dimensions (ie: physical evidence, reliability, responsiveness, assurance, empathy, information systems). The findings reveal that the responsive tangibles dimension shows the highest negative gap, while the reliability dimension has the lowest negative gap among all dimensions. So the conclusion is that overall improvements must be made in order to be able to provide optimal service for users of educational services, especially in West Sumatra, Indonesia.